Alternative Bearing Surfaces in Total Joint Replacement 1998
DOI: 10.1520/stp12831s
|View full text |Cite
|
Sign up to set email alerts
|

Glassy Alloys as Potential Bearing Surfaces for Orthopaedic Implants

Abstract: Glassy (amorphous) metals have some unique properties that may render them attractive candidates for the coating of metal-implant bearing surfaces. Metastable glasses of metal alloys, with uniform compositions and homogeneous structures that are not attainable under usual quasi-equilibrium processing conditions, can often be made to produce alloys with exceptional corrosion resistance and high hardness. The absence of secondary phases argues for resistance to abrasive and asperity-initiated wear. One method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The latter are attractive candidates for the coating of metal implant bearing surfaces, for example in TJR. Indeed, Tesk et al [237,238] suggested a while ago glassy Co–P, Co–Cr–C and Cr–C coatings for this purpose.…”
Section: Common Metallic Biomaterials and Their Corrosion Performancementioning
confidence: 99%
“…The latter are attractive candidates for the coating of metal implant bearing surfaces, for example in TJR. Indeed, Tesk et al [237,238] suggested a while ago glassy Co–P, Co–Cr–C and Cr–C coatings for this purpose.…”
Section: Common Metallic Biomaterials and Their Corrosion Performancementioning
confidence: 99%